The Relationship between Wisdom and both Emotional Intelligence and Creative Thinking Abilities among Female Teachers, Suffering from Psychological Stresses - Al-Huwailah , Amthal Hadi (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims at highlighting the relationship between wisdom and both emotional intelligence and creative thinking abilities among female teachers and examine differences in these variables between who were subject to psychological stress comparted to those who were not exposed. Methods: The descriptive correlative approach was used. The study sample consisted of (200) secondary school teachers, (90) of the female teachers exposed to psychological stress and (110) who were not exposed to psychological stress. The teachers’ ages ranged between 25 and 55 years. The Emotional Intelligence Scale, the Stress Scale, and the Gliford Creative Abilities Scale and the Wisdom Scale were applied. Results: The study showed that there were positive correlations between the components of wisdom and both of emotional intelligence and creative thinking abilities. Moreover, it was found that there were differences among female teachers exposed to psychological stress and those non-exposed to psychological stress in emotional intelligence, creative thinking abilities and wisdom in the direction of the non-exposed to psychological stress. Conclusions: It was observed that wisdom, emotional intelligence, and creative thinking abilities reduce psychological stress among female teachers, and thus, psychological support must be provided to all female teachers, work to increase their levels of adaptation, and counseling programs should be prepared to raise the efficiency of female teachers within the family and at work.